Boletim and Arquivos: scientific communication until the creation of the Revista de Saúde Pública - Marques, Maria Cristina da Costa (Rev Saude Publica, 2016)
Based on historical references of scientific communication, we analyzed the issues of the Boletim do Instituto de Higiene de São Paulo and of the Arquivos da Faculdade de Higiene e Saúde Pública da Universidade de São Paulo. Published respectively from 1919 to 1946 and from 1947 to 1966, they totaled 120 issues. In their 48 years of publication, their goal was to disseminate the scientific production of the institution and to legitimize the theoretical debate of the field, in addition to supporting the public health intervention models, written by leading researchers of the institution and by contributors and managers in the field of public health. Both the Boletim and the Arquivos were recognized as scientific communication of national reference, and have laid the foundations for the creation of the Revista de Saúde Pública, in 1967.